Medical Science Faculty marks 25 years - (:unkn) unknown (The Sunday Times, 2018)
The Medical Faculty of the University of Sri Jayewardenepura will mark 25 years in March 2018. In honour of this ocation and to mark the occupation of the faculty’s newly-constructed Phase IV building an all-night Pirith ceremony was held on the19th of January 2018 with the participation of the monks led by the Chancellor Ven. Prof. Bellanwila Wimalaratana Nayaka Thera followed by an alms-giving on the 20th in the new building complex. The Faculty held an all night Pirirth scession